1995
DOI: 10.1209/0295-5075/30/1/010
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Function of YNi 2 B 2 C between 10 meV and 50 eV

Abstract: PACS. 74.72Bk -Y-based compounds. PACS. 78.00 -Optical properties of condensed-matter spectroscopy and other interactions of PACS. 79.20Kz -Other electron-impact emission phenomena. matter with particles and radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
23
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 11 publications
(2 reference statements)
6
23
1
Order By: Relevance
“…The plasma frequencyhω pl =4.4 eV is in accord withhω pl =4.25 eV obtained in Ref. 34. From the obtained v F 's it is concluded that ω pl is mainly related to the second weakly coupled band.…”
supporting
confidence: 88%
“…The plasma frequencyhω pl =4.4 eV is in accord withhω pl =4.25 eV obtained in Ref. 34. From the obtained v F 's it is concluded that ω pl is mainly related to the second weakly coupled band.…”
supporting
confidence: 88%
“…[65][66][67] The calculated imaginary part of the optical dielectric tensor ⑀ 2 () for YNi 2 B 2 C is shown in Fig. 5 where Eʈa and Eʈc represent the electric field parallel to the crystallographic axes a and c, respectively.…”
Section: Calculated Raman Spectrum For Yni 2 B 2 Cmentioning
confidence: 99%
“…A molecular nickel carborane complex has been synthesized by inorganic chemists 8 and the inclusion of nickel in other boron rich solids is well established. Nickel is a common component in the boron carbide superconductors 9 and the reactions of nickel with boron phosphide have been investigated. [10][11] Nickelocene, Ni͑C 5 H 5 ͒ 2 , has been shown to be a suitable source compound for the deposition of nickel containing thin films.…”
Section: Introductionmentioning
confidence: 99%